PKM ALAT PEMERAS JAHE BAGI USAHA MINUMAN KESEHATAN “MBA IMA” - Eko Yudo; Ariyanto Ariyanto; Zaldy Kurniawan (Jurnal Pengabdian Masyarakat Polmanbabel, 2023)
The development of processed products from ginger has recently begun to grow, especially with the presence of the Covid 19 virus which has an impact on all countries, especially for Indonesia. Preparations made from ginger and other spices are believed to maintain stamina for the human body. Processed products from ginger ranging from ginger wedang, ginger candy and instant ginger. Some of the benefits of instant ginger for health include warming the body, relieving colds, reducing menstrual pain and many other uses. Some types of ginger that are commonly developed in Indonesia include red ginger, small and large white ginger. With the different characteristics and benefits of each type of ginger, the ginger that is often processed into powdered ginger or instant ginger is red ginger. In Bangka Belitung, especially Bangka district, Mrs. Salimah has been processing this instant ginger since3 years ago, until now she is still producing this red ginger instant drink. The problem faced by Mrs. Salamah as a community service partner is because the equipment used to produce instant ginger still uses manual or makeshift equipment so that the resulting production is not optimal. To cover the lack of partners' problems, community service will provide solutions to partners, namely in the form of TTG machines (appropriate technology) to support instant ginger production. By using this squeezer machine, Mrs. Salimah can extort 5 kg in 15 minutes compared to using her hands, 5 kg can take 30 minutes.